Peristomal skin changes: therapeutic education on prevention and nursing interventions on management - Gloria Dorigo (Infermieristica Journal)
Introduction: for the person with an ostomy it is very important to have intact peristomal skin, because there is a certainty that the ostomy pouching system adheres to the skin; on the other hand, with altered skin there is a greater risk that the ostomy pouching system detaches with consequent infiltration of the effluents and contact with the peristomal skin, showing skin alterations and further compromising the person's quality of life.